Ibu Rumah Tangga yang Bekerja sebagai Ojek Online (Studi Fenomenologi) - Sri Endang Herudiati (STIT Syekh Muhammad Nafis Tabalong, 2023)
This research aims to find out the reasons why women work as online motorcycle taxi drivers and the factors that influence the existence of women who work as online motorcycle taxi drivers. This research discusses the phenomenon of women working as online motorcycle taxi drivers. So using qualitative methods. Data collection was carried out using interview techniques (in depth interviews) and observation. The number of respondents in this study was 4 women who worked as online motorcycle taxi drivers. The research results show that work as an online motorcycle taxi driver is carried out to help families meet economic needs. So women must be able to divide their time between family and work.